Sense and features of the citizenship in Ukraine - Пильгун, Наталія Василівна; Бузун, Ольга Олегівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The issue of cityzenship is relevant and interesting both for Ukraine either for the whole world. Among scientists, the the main essence and meaning studied Thomas Hobbes, who was the first to raise the issue of the role of the person and of the citizen in the society, to broaden relationships between the community and the state, and he was first to use the term "civil society", which later influenced the formation of citizenship, V. V. Lazarev observed that the state brings people together in a single unit, and their membership of a particular state is covered by the concept of "citizenship". Y. M Todyka exposes that a permanent legal connection between the person and the state is reflected in their mutual rights and obligations. The main purpose of the research is to highlight the essence, meaning and problematic questions according to the acquisition and termination the citizenship in Ukraine, the analysis of international practices according to making solutions about the complicated side of the citizenship and especially about the dual citizenship based on the international experience. According to the history, citizenship institution appeared quite among all the states and traditionally considered jurisprudence and practice as a stable legal connection between the individual and the state, which is expressed by the quantity of their mutual rights and obligations. Nowadays there are many definitions of the institute of the citizenship in the science of Ukraine and in international law. All definitions are different and some of them are particularly opposite. The Law "On Citizenship of Ukraine" which is dated 18th of January, 2001 determines the legal status of citizenship Ukraine, bases and procedure for acquiring and termination, the competency of state authorities which are involved in the process according to the citizenship of Ukraine, the order of applications against decisions about the citizenship, and the actions or inaction of the government bodies, their officials and officers. Citizenship is on a such stage, which allows the status of citizen partly be involved in the political, economical, juditional and cultural life of society and the state. It is known, that main features of the citizenship as a particular connection with the state are: firstly, the existence of a legal procedure; secondly, limitlessness in space and time; Thirdly, the maximal temper of the mutual rights and obligations.